2022
DOI: 10.3390/ma15248925
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Deformation Behavior of Additive-Manufactured IN738LC Superalloys from Virgin and Reused Powders

Abstract: In laser powder bed fusion (L-PBF), most powders are not melted in the chamber and collected after the printing process. Powder reuse is appreciable without sacrificing the mechanical properties of target components. To understand the influences of powder reuse on mechanical performance, a nickel-based superalloy, IN738LC, was investigated. Powder morphology, microstructure and chemical compositions of virgin and reused powders were characterized. An increase in oxygen content, generally metallic oxides, was l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Similar to the steel, the change of composition in the reused Inconel 718 alloy powders seems to be limited to the increase of oxygen content [35,199,201,234], while the variation of other elements, such as C, N, and H, is marginal [182,194,199,234]. The increased oxygen content is in the form of Cr, Al, and Ti-rich oxides with a size of several micrometers [35,182,201] attaching to the surface layer of reused Inconel 718 powders. As for the microstructure of Hastelloy X powders [198], both the virgin and reused powders show no obvious texture (figures 12(a-i) and (a-iii)).…”
Section: Powder Reusability Of Nickel Alloymentioning
confidence: 92%
See 4 more Smart Citations
“…Similar to the steel, the change of composition in the reused Inconel 718 alloy powders seems to be limited to the increase of oxygen content [35,199,201,234], while the variation of other elements, such as C, N, and H, is marginal [182,194,199,234]. The increased oxygen content is in the form of Cr, Al, and Ti-rich oxides with a size of several micrometers [35,182,201] attaching to the surface layer of reused Inconel 718 powders. As for the microstructure of Hastelloy X powders [198], both the virgin and reused powders show no obvious texture (figures 12(a-i) and (a-iii)).…”
Section: Powder Reusability Of Nickel Alloymentioning
confidence: 92%
“…There is no obvious microstructure variation, including grain size, dendrite size, and texture, when reusing the Inconel 718 or Inconel 738 powders [182,199,201]. For instance, it is found that the L-PBF Inconel 718 samples printed with both virgin and reused powders exhibit continuous γ matrix and flower-shaped γ ′ precipitates, as well as similar texture and grain size [234] (figures 12(b-i) and (b-iii)).…”
Section: Powder Reusability Of Nickel Alloymentioning
confidence: 98%
See 3 more Smart Citations